Bangunan Pendidikan Karakter Di Indonesia - Esti Zaduqisti (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Holistic education model using the method of knowing the good, feeling the good, and acting the good. Knowing the good can easily be taught because of cognitive knowledge only. After knowing the good, it must be grown feeling loving the good, that is how to feel and love of virtue into a machine that can make people always want to do something good. Once accustomed to do good things, the good acting then it turns into a habit. The formulation is embodied in a program named: education culture and national character, which is interpreted as an education that develops the cultural values and national character in students. Keywords : Character education and national character.